Implementasi Digital Marketing Berbasis Wordpress pada Ichi Hydroponic Store Madiun - Okky Aldhy Try Cahyo; Dimas Setiawan; Mei Lenawati (JURNAL PILAR TEKNOLOGI Jurnal Ilmiah Ilmu Ilmu Teknik, 2022)
Currently, Ichi Hydroponic Store products have been marketing its products using digital marketing through WhatsApp social media. Because product marketing is only through WhatsApp, the promotions carried out by the Ichi Hydroponic Store are only aimed at customers who save WhatsApp numbers. Ichi Hydroponic Store, the researchers developed WordPress as a means of marketing Ichi Hydroponic Store products to reach a wider market. The approach in this study uses the Waterfall model. The waterfall model is a classical model that is systematic and sequential in building software. The name of this model is the Linear Sequential Model. This model is often called the classic life cycle or the waterfall method. The Usability Test results show that the web design is good and can be accepted by the user. The implementation of digital marketing based on WordPress provides an increase in revenue of 30.97% from the comparison ten days before and after the web release. The website is expected to be used properly, and the owner can operate it himself.